They tend to bite off more - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Insect Pests in Tropical Forestry By M R Speight & F R Wylie, CABI Publishing, 2000. 320 pp. ISBN 085199461X GBP 30 Euro 48.80